Quantum mechanics' return to local realism - Tu, Runsheng (Cambridge Scholars Publishing, 2018)
This book proposes a model of the light knot electronic structure and the theory of quantum inverse measurement, showing that diffraction experiments can be explained by directional quantization. It points out that there exists a logical loophole in the interpretation process of quantum entanglement, and proves that there is a paradox in the uncertainty relationship. As such, the book lays the foundation for the establishment of local-realism quantum mechanics and successfully establishes the quantum mechanics of localized realism and determinism is successfully established. It will appeal to.